ANALYSIS OF THE USE CREATIVE SPACES AND COWORKING USE FOR PROJECT DEVELOPMENT IN A SOCIAL NETWORK - Fragnan Junior, V. L. [UNESP]; Botura Junior, G. [UNESP]; Chova, L. G.; Martinez, A. L.; Torres, I. C. (Iated-int Assoc Technology Education & Development, 2018)
Coworking spaces are physical spaces destined to the meeting of individuals who seek flexibility and autonomy in the work, this characteristic of spaces are notable mainly for their capacities of interaction between professionals with diversity of knowledge and experiences, in this way spaces have organizations capable of manifesting the informal exchange of knowledge. Considering the reality of the use of creative space and coworking the article presents results of quantitative analysis between the creation of an online and face - to - face project divided into two realities, which aimed to identify approaches in the treatment of uses of creative spaces and the use of coworking for the development of projects in a project developed for the social network. In the face-to-face analysis was used a creative room and coworking in the Public School Youth Park for the development of the project in social networks. The accomplishment between the results obtained in the projects developed in these spaces and outside of it allowed to identify the influence of its use provided an analysis of the activity carried out between face-to-face with use of space and online to mediate the exchange of knowledge, in addition to the existing relationship between its organizational ergonomics of space and the quality of what was produced. The results were categorized and show that the use of creative space had a relevance in their activities than the projects were of this reality.
Keywords: Coworking; organizational ergonomics; social network